2010
DOI: 10.5539/jmr.v2n4p93
|View full text |Cite
|
Sign up to set email alerts
|

Necessary and Sufficient Condition of Existence for the Quadrature Surfaces Free Boundary Problem

Abstract: Performing the shape derivative (Sokolowski and Zolesio, 1992) and using the maximum principle, we show that the so-called Quadrature Surfaces free boundary problemhas a solution which contains strictly the support of f if and only ifWhere C is the convex hull of the support of f . We also give a necessary and sufficient condition of existence for the problem Q S ( f, k) where the term source f is a uniform density supported by a segment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…B being the unit ball in R 2 . Notice that in the special case where g ≡ k = const., the the condition above becomes a > 2k and it is necessary and sufficient condition of existence for QS(a, k) [3]. C Ω being the unique Cheeger set of Ω.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B being the unit ball in R 2 . Notice that in the special case where g ≡ k = const., the the condition above becomes a > 2k and it is necessary and sufficient condition of existence for QS(a, k) [3]. C Ω being the unique Cheeger set of Ω.…”
Section: Discussionmentioning
confidence: 99%
“…The method used by Gustafsson and Shahgholian goes back to K. Friedrichs [18], or even to T. Carleman [11], and was considerably developed by H. W. Alt and L. A. Caffarelli [1]. Recently, by combining the maximum principle to the compatibility condition of the Neumann problem, Barkatou et al [3] gave, |∇u C | > k on ∂C as a sufficient condition of existence for Q S (f, g). Later, Barkatou [2] showed that this problem admits a solution if and only if the condition…”
Section: Introductionmentioning
confidence: 99%
“…In [21], in order to get solutions to Problem QS(f, g), A. Henrot used the method of subsolutions and supersolutions introduced by A. Beurling [8]. By combining the maximum principle to the compatibility condition of the Neumann problem, Barkatou et al [3] gave, |∇u C f | > k on ∂C f as a sufficient condition of existence for QS(f, g). Later, Barkatou [2] showed that this problem admits a solution if and only if the condition…”
Section: Introductionmentioning
confidence: 99%